2020
DOI: 10.18662/po/11.1sup1/131
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Corporate Culture Formation of Specialists of Social Institutions

Abstract: The theoretical approaches to define the scientific definition "corporate culture" in the sociological, economic, psychological and pedagogical contexts have been analyzed. The corporate culture of a social institution is understood as a system of collective norms, beliefs, values and traditions of joint activity of employees, aimed at achieving the strategic goals of the organization. Based on the results of using standardized methods, the conducted monitoring research reflects the role of corporate culture f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…The study found that the ability to constructively resolve conflict situations and prevent their occurrence, gaining knowledge and experience of conflict-free management is one of the most important areas of professional development of leaders of all ranks, a sign of high readiness of modern officers to perform professional duties. Border guard unit with a healthy socio-psychological climate is characterized by the ability to carry out high-quality operational and service activities, to maintain the necessary state of discipline, combat and mobilization readiness of the unit (Moroz, 2020;Soroka et al, 2020). The readiness of border guard officers to manage conflict situations is an important component of their professional readiness, as it provides the ability to effectively organize the implementation of operational and service tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the ability to constructively resolve conflict situations and prevent their occurrence, gaining knowledge and experience of conflict-free management is one of the most important areas of professional development of leaders of all ranks, a sign of high readiness of modern officers to perform professional duties. Border guard unit with a healthy socio-psychological climate is characterized by the ability to carry out high-quality operational and service activities, to maintain the necessary state of discipline, combat and mobilization readiness of the unit (Moroz, 2020;Soroka et al, 2020). The readiness of border guard officers to manage conflict situations is an important component of their professional readiness, as it provides the ability to effectively organize the implementation of operational and service tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the essence and content of the notions "culture" and "organization", as well as the results of the analysis of psychological and pedagogical literature on the problem of the study, it was determined that the concept "organizational culture of the border guard officer" should be interpreted as a professionally important property, which includes knowledge about the mission and value of the border agency, the ability to maintain and promote cohesion of the border guard team, the abilities and skills to comply with professional standards in interpersonal interaction and performance of border security tasks, self-organization and mobilization. In the structure of organizational culture as a personal formation, it is advisable to distinguish several structural and functional components, primarily personal, cognitive and behavioural (Harris, et al, 2007;Soroka, et al, 2020).…”
Section: Essence Structure Content and Diagnostics Of The Organizational Culture Of Border Guard Officersmentioning
confidence: 99%
“…The relevance of this problem investigation is also conditioned by the requirements placed on the representatives of the border agency. After all, one of the tasks is to increase the capacity of their staff by improving of the quality of their professional training in order to be able to effectively respond to new challenges in the performance of their duties (ZALITIS, ZUKOVA, MADZULE, 2016;SOROKA et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%